2017
DOI: 10.1039/c7cp03292g
|View full text |Cite
|
Sign up to set email alerts
|

Magnetite hollow microspheres with a broad absorption bandwidth of 11.9 GHz: toward promising lightweight electromagnetic microwave absorption

Abstract: High-performance magnetite-based hollow spheres with the advantages of low density and low loading content are promising as an ideal lightweight electromagnetic (EM) wave absorption candidate. However, the effective preparation methods for these hollow spheres are still limited, and as a result, materials design and practical applications based on their size-dependent EM microwave attenuation properties are poorly accessible. In this study, high quality magnetite hollow spheres were successfully prepared by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…2019, 9, 3877 2 of 17 attracted much interest in the field of EM wave absorption. However, Fe 3 O 4 as an absorptive material have some limitations such as the rapid decrease in permeability value at microwave frequency, large density, ease of oxidation and mismatch of impedance which impedes its performance as an ideal MAM [6,7].Recently, several research efforts have been geared towards improving the microwave absorption performance (MAP) of Fe 3 O 4 . For example, Mingxu et al [8] fabricated hollow Fe 3 O 4 nanoparticles via solvothermal route, with the aim of reducing its density while retaining good magnetic properties for efficient MAP.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2019, 9, 3877 2 of 17 attracted much interest in the field of EM wave absorption. However, Fe 3 O 4 as an absorptive material have some limitations such as the rapid decrease in permeability value at microwave frequency, large density, ease of oxidation and mismatch of impedance which impedes its performance as an ideal MAM [6,7].Recently, several research efforts have been geared towards improving the microwave absorption performance (MAP) of Fe 3 O 4 . For example, Mingxu et al [8] fabricated hollow Fe 3 O 4 nanoparticles via solvothermal route, with the aim of reducing its density while retaining good magnetic properties for efficient MAP.…”
mentioning
confidence: 99%
“…2019, 9, 3877 2 of 17 attracted much interest in the field of EM wave absorption. However, Fe 3 O 4 as an absorptive material have some limitations such as the rapid decrease in permeability value at microwave frequency, large density, ease of oxidation and mismatch of impedance which impedes its performance as an ideal MAM [6,7].…”
mentioning
confidence: 99%
“…In recent decades, magnetic materials such as ferrites, magnetic oxides and magnetic metals have been extensively applied in the EM wave absorption area as they possess simultaneous dielectric and magnetic losses. For instance, Shanenkov et al 9 synthesized the hollow ferritic microspheres via the plasma dynamic method. Their experimental results demonstrated that the hollow magnetic microspheres exhibited a minimum reflection loss (RL) value of −36 dB and ultra-wide effective absorption bandwidth of 11.9 GHz at only 2 mm.…”
Section: Introductionmentioning
confidence: 99%
“…However, the derived electromagnetic wave pollution and electromagnetic interface problem have seriously restricted their further development [1,2]. Depending on the electromagnetic loss theory, a feasible way to solve such problems is to develop high performance absorption materials [3]. The shielding effectiveness of the electromagnetic shielding materials based on wood due to low cost-effective, lightweight and easy to manufacture, indicating that it had broad prospects.…”
Section: Introductionmentioning
confidence: 99%